A Quantum Chemical Study on Structures and Electronic (Hyper)polarizabilities of 2, 2′-Biselenophene Rotamers. (26th December 2013) - Alparone, Andrea
Abstract : Geometries, IR and Raman spectra, nucleus independent chemical shifts, and static electronic (hyper)polarizabilities of the equilibrium conformations of 2, 2′-biselenophene were determined in vacuum using density functional theory (DFT) computations. At the DFT-PBE0/6-31G+pdd′ level the antigauche structure characterized by the Se- C 2 - C 2 ′ -Se dihedral angle of 157° is the global minimum, whereas the syngauche rotamer (Se- C 2 - C 2 ′ -Se = 40°) lies ca. 0.7 kcal·mol −1 above the antigauche form. The structural and spectroscopic properties as well as the electronic polarizability of the antigauche are similar to those of the syngauche structure. On the other hand, the dipole moments and first-order hyperpolarizabilities are strongly influenced by the conformational characteristics, increasing by ca. a factor of five when passing from the antigauche to the syngauche form.